Synthesis and immunological effects of C14-linked 4, 5-epoxymorphinan analogues as novel heroin vaccine haptens. Issue 3 (19th April 2021) - Gutman, Eugene S.; Irvin, Thomas C.; Morgan, J. Brian; Barrientos, Rodell C.; Torres, Oscar B.; Beck, Zoltan; Matyas, Gary R.; Jacobson, Arthur E.; Rice, Kenner C.
Abstract : Three novel opiate surrogates with the linker at C14, 1 (6, 14-AmidoHap), 2 (14-AmidoMorHap), and 3 (14-AmidoHerHap) were conjugated to tetanus toxoid (TT) and tested as heroin vaccines. The C3 and C6 moieties are crucial in antibody selectivity. Abstract : Active immunization is being explored as a potential therapeutic to combat accidental overdose and to mitigate the abuse potential of opioids. Hapten design is one of the crucial factors that determines the efficacy of a candidate vaccine to substance abuse and remains one of the most active areas of research in vaccine development. Herein we report for the first time the synthesis of three novel opiate surrogates with the linker attachment site at C14, 1 (6, 14-AmidoHap), 2 (14-AmidoMorHap), and 3 (14-AmidoHerHap) as novel heroin haptens. The compounds 1, 2, and 3 are analogues with different substituents at C6: an acetamide, a hydroxyl moiety, and an acetate, respectively. All three haptens had a phenolic hydroxyl group at C3. The haptens were conjugated to the tetanus toxoid carrier protein, adjuvanted with liposomal monophosphoryl lipid A/aluminum hydroxide and were tested in mice in terms of immunogenicity and efficacy. Immunization of mice resulted in antibody endpoint titers of >10 5 against all the haptens. Neither of the conjugates of 1, 2, and 3 had induced antibodies with selectivity broad enough to recognize and bind heroin, 6-AM, and morphine resulting in little to no protection against the antinociceptive effects of heroin in vivo . Only the mice immunized with conjugate 3 were partially protected against heroin-induced antinociception. These results contribute to the growing body of knowledge that the linker position and the subtle structural differences in the hapten scaffold impact the selectivity of the induced antibodies. Together, these highlight the importance of rational hapten design for heroin vaccine development.